Assessment of E-government in EU countries - Ardielli, Eva; Halásková, Martina (Univerzita Pardubice, 2015)
E-government is one of the priority trends of public administration modernization in the EU countries (28). The paper deals with the evaluation of the e-government state, because of the importance of e-government as a tool of progressive modernization of public administration. The presented research is specifically focused on the comparison of the current state of e-government in the European Union and the assessment of the position of the Czech Republic on the basis of e-government indicators. The attention is paid to e-government indicators monitored by international institutions (United Nations, European Union and Eurostat) using TOPSIS method. Evaluated data describe the state of e-government in EU countries in the year 2013. In the research, there was selected the final list of variants (monitored EU countries) and criteria (e-government indicators - User Centric Government, Transparent Government, Citizen Mobility, Business Mobility, Key Enablers, Online Service Index, E-Participation Index, Individuals Using Internet and Enterprises Using Internet). The results of the evaluation of the EU countries in terms of the state of e-government by TOPSIS method in the 2013 acknowledged, that the best ranking in this field obtained Estonia, then the Scandinavian countries (Finland, Sweden) and Malta. The worst state of e-government was reported in Romania, Bulgaria and Croatia. The Czech Republic then in the evaluation of e-government occupied the 24th position across all EU countries (28).
Keywords: assessment; E-Government; EU countries; public administration; TOPSIS; H11; H83